Exploring Cadets’ Challenges in Learning Maritime English in the Technological Era - Rahadianto, Piping; Pera Fitria, Yuli; Yusrah (English Education: Jurnal Tadris Bahasa Inggris, 2026)
The rapid advancement of digital technologies has transformed maritime education, creating new opportunities and challenges for Maritime English learning. As English serves as the primary language of international maritime communication, maritime cadets are expected to develop not only general English proficiency but also specialized communicative competence required for shipboard operations. This study aimed to explore the challenges experienced by maritime cadets in learning Maritime English within the technological era. Employing a qualitative descriptive research design, the study was conducted at Politeknik Pelayaran Malahayati Aceh, Indonesia. Twenty-four cadets enrolled in the Marine Electrical Officer program participated in semi-structured interviews. Data were analyzed thematically to identify recurring patterns and perceptions related to technology-mediated Maritime English learning. The findings revealed that cadets experienced both benefits and challenges associated with technology-enhanced learning. Digital tools such as mobile applications, learning management systems, and maritime simulators increased learning flexibility, authenticity, and learner autonomy. However, participants reported significant challenges related to vocabulary retention, listening comprehension, Standard Marine Communication Phrases (SMCP) recall, pronunciation practice, and communication under time pressure. These linguistic difficulties were frequently exacerbated by technical and infrastructural barriers, including limited access to digital devices, unstable internet connectivity, software malfunctions, and insufficient digital literacy. Furthermore, technological challenges contributed to psychological consequences such as anxiety, frustration, reduced self-confidence, and decreased motivation. To overcome these obstacles, cadets relied heavily on peer support, low-technology learning strategies, and repeated practice. Participants also emphasized the importance of improved institutional support, including digital literacy training, enhanced technological infrastructure, accessible learning platforms, and continuous instructor guidance. The study concludes that while technology offers considerable pedagogical benefits for Maritime English education, its effectiveness is strongly influenced by digital access, technological competence, and institutional support. Therefore, successful implementation of technology-mediated Maritime English learning requires a balanced approach that integrates technological innovation with inclusive educational practices and learner-centered support systems.